Contribución de bacterias endófitas nativas en la acumulación de nutrientes en poaceas altoandinas - Santillana Villanueva, Nery (2021)
The aim of this research was to determine native endophytic bacteria contribution in the accumulation of nutrients in three high Andean Poaceae at 4116 m above sea level. Macro and micronutrients content in the aerial biomass of Calamagrostis vicunarum, Festuca dolichophylla and Muhlenbergia ligularis inoculated with 19 endophytic bacteria was determined, which were compared with three controls (basic fertilization, chemical fertilization and without any application). The results in Calamagrostis vicunarum showed that four isolates (13, 19, 12 and 16) contributed between 15.2 and 35.6% in the accumulation of S, Ca, Na, Mg, P, K and N (macronutrients) and Fe, B, Zn, Mn, Cu and Mo (micronutrients). In Festuca dolichophylla two isolates of B. mycoides (16 and 14), Paenibacillus tundrae (10) and Staphylococcus warneri (7) contributed between 8.6 and 25.9% in the accumulation of S, Ca, Mg, P and K (macronutrients) and B, Zn, Mn and Cu (micronutrients). In Muhlenbergia ligularis, Bacillus simplex (2), B. mycoides (19 and 15), P. xylanexedens (17) and P. amylolyticus (9) bacteria contributed between 10.7 and 73.6% in the accumulation of Na, N, K, Mg, S, P and Ca (macronutrients) and Cu, Mo, B, Fe, Zn and Mn (micronutrients). These results show the endophytic bacteria potential to improve the nutrient content in high Andean Poaceae, although they show some species specificity in the effect.